2013
DOI: 10.1038/jcbfm.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms in Cerebral Ischemia

Abstract: Treatment efficacy for ischemic stroke represents a major challenge. Despite fundamental advances in the understanding of stroke etiology, therapeutic options to improve functional recovery remain limited. However, growing knowledge in the field of epigenetics has dramatically changed our understanding of gene regulation in the last few decades. According to the knowledge gained from animal models, the manipulation of epigenetic players emerges as a highly promising possibility to target diverse neurologic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 148 publications
(219 reference statements)
1
72
0
1
Order By: Relevance
“…The increase in acH3K24 content detected after 3 sessions of MHH promoted the formation of euchromatin and facilitates the delivery of transcription factors (CREB, Hif, NF-κB, c-Fos, etc.) to target gene promoters [5,11,14]. The increase in meH3K9 content caused by SHH and single MHH promoted chromatin condensation (formation of heterochromatin) and reduced accessibility of target genes for transcription factors [5,12,15].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The increase in acH3K24 content detected after 3 sessions of MHH promoted the formation of euchromatin and facilitates the delivery of transcription factors (CREB, Hif, NF-κB, c-Fos, etc.) to target gene promoters [5,11,14]. The increase in meH3K9 content caused by SHH and single MHH promoted chromatin condensation (formation of heterochromatin) and reduced accessibility of target genes for transcription factors [5,12,15].…”
Section: Resultsmentioning
confidence: 98%
“…Acetylation, methylation, phosphorylation, and ubiquitination of histones largely determine the access of transcription factors to the target genes [3,5,13,14]. DNA methylation leads to gene repression [11]. The role of epigenetic mechanisms regulating activities of various genes in cell reactions to hypoxia has been in the focus of recent research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that in experimental models of cerebral ischemia in vivo there is an imbalance in the acetylation/deacetylation homeostasis that can be prevented by using HDAC inhibitors that restore histone acetylation levels (see for reviews: (Langley et al, 2009;Gibson and Murphy, 2010;Schweizer et al, 2013). Along this line, we have previously demonstrated that in the ischemic brain tissue of rats subjected to middle cerebral artery occlusion for 6 h, histone H3 acetylation levels were drastically reduced, with no evidence for a concomitant change of histone acetyl-transferase or deacetylase activities, and that treatment with the HDAC inhibitor SAHA increased histone acetylation in the normal brain and prevented deacetylation in the ischemic brain (Faraco et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (reviewed in: Langley et al, 2009;Gibson and Murphy, 2010;Schweizer et al, 2013) have shown that histone acetylation is reduced following cerebral ischemia and that class I, II and IV HDAC inhibitors are able to ameliorate neuronal death and cognitive deficits following transient (Endres et al, 2000;Ren et al, 2004;Qi et al, 2004;Faraco et al, 2006;Yildrim et al, 2008;Wang et al, 2012) and permanent Langley et al, 2008;Kim et al, 2009) focal ischemia and in a model of transient global ischemia (Xuan et al, 2012). These effects appear to be due to the maintenance of histone acetylation levels, the expression of cell survival (Bcl-2, Bcl-XL, Hsp70) and regenerative (BDNF) pathways, and the downregulation of pro-inflammatory genes (COX-2, iNOS, TNF-a, IL-b) (Faraco et al, 2006;Kim et al, 2007Kim et al, , 2009.…”
Section: Disordersmentioning
confidence: 99%